Thermal conductivity of advanced TiC reinforced metal matrix composites for polymer processing applications. (January 2015) - Wilzer, Jens; Windmann, Matthias; Weber, Sebastian; Hill, Horst; Bennekom, André van; Theisen, Werner
Tools used for fabricating polymers are often required to have low thermal conductivities, e.g. for pelletizing, because this lowers the risk of the polymer nozzle being obstructed by molten polymer solidifying as it exits. Latterly, advanced corrosion and wear resistant metal matrix composites (MMCs) are used for pelletizing tools. Therefore, with respect to polymer processing it is important to know how the thermal conductivity of MMC gets influenced by hard phase and metal matrix contribution. In this study, the thermal conductivity of a TiC reinforced corrosion and wear resistant MMC gets analyzed. Especially the influence of chemical interdiffusion between TiC and metal matrix on the resulting thermal conductivity gets analyzed. It is shown that changes in the chemical composition lead to distinct decrease in thermal conductivity of the TiC which has to be considered when MMC thermal conductivities have to be examined.